Pengaruh Promosi Media Online terhadap Keputusan Pembelian Produk Hijab - Riyanto Setiawan Suharsono; Rini Purnama Sari (STIE Kertanegara Malang, 2019)
The observation purpose is to testing influence of online media promotion against the purchase decision. The population is 500 active consumers of Alif Galeri Hijab Sidoarjo. Data used is result of answers from consumer questionnaires which distributed to all active consumer of Alif Galeri Hijab Sidoarjo. The number of sample used is 83people through Slovin formula. The analyze technic used is simple linear regression with purpose to get the overview of the effect from online media promotion on purchasing decisions.The results of the observation isrepresented by the formula : Y = 10,786 + 0,750x. The formula is the result of validity test, reability test, normality test, heteroskedasticity test, partial test and coefficient of determination. The test show that every 1% increase of online media promotion then the purchase of decision will increase 75%. It can be concluded if online media promotion have a significant positive effect against the purchase decision.